A fluorescent sphingolipid binding domain peptide probe interacts with sphingolipids and cholesterol-dependent raft domainss⃞ - Sarita Hebbar; Esther Lee; Manoj Manna; Steffen Steinert; Goparaju Sravan Kumar; Markus Wenk; Thorsten Wohland; Rachel Kraut (Journal of Lipid Research, 2008)
We have designed a tagged probe [sphingolipid binding domain (SBD)] to facilitate the tracking of intracellular movements of sphingolipids in living neuronal cells. SBD is a small peptide consisting of the SBD of the amyloid precursor protein. It can be conjugated to a fluorophore of choice and exogenously applied to cells, thus allowing for in vivo imaging. Here, we present evidence to describe the characteristics of the SBD association with the plasma membrane. Our experiments demonstrate that SBD binds to isolated raft fractions from human neuroblastomas and insect neuronal cells. In protein-lipid overlay experiments, SBD interacts with a subset of glycosphingolipids and sphingomyelin, consistent with its raft association in neurons. We also provide evidence that SBD is taken up by neuronal cells in a cholesterol- and sphingolipid-dependent manner via detergent-resistant microdomains. Furthermore, using fluorescence correlation spectroscopy to assay the mobility of SBD in live cells, we show that SBD's behavior at the plasma membrane is similar to that of the previously described raft marker cholera toxin B, displaying both a fast and a slow component. Our data suggest that fluorescently tagged SBD can be used to investigate the dynamic nature of glycosphingolipid-rich detergent-resistant microdomains that are cholesterol-dependent.